Overcoming Legacy Processing in Photographic Collections through Collaboration and Digital Technologies. Issue 2 (June 2018) - Holtze, Terri; Howard, Rachel; Kuehn, Randy; Pattillo, Rebecca; Reilly, Elizabeth
In the 1960s, a Louisville photography studio began donating its negatives, prints, and invoices to the University of Louisville Photographic Archives. The Caufield & Shook collection remains a significant primary source for local history and a prime candidate for digitization. Unfortunately, on its receipt, nonarchivists processed the collection with little documentation of original order or organizational decision making. Additionally, workflow choices were determined largely by the desire to maximize student labor. In 2017, the digital initiatives librarian worked with in-house application developers and archives staff to create a workflow that has significantly sped up the process of making this valuable photographic collection accessible online. This article describes how archivists recovered from the poor processing decisions, used technology to enhance the digitization workflow, and developed a list of best practices for future processing and digitization of large photographic collections.